Analysis of Errors and Complications Found in the Use of Endocanal Constructions Used in Dentistry - Erkinova Sevinch Shokhimardonovna; Hadzhimuradov Burkhan Ravshanovich (Scientific Trends, 2024)
Restoring defects in the hard tissues of the teeth is one of the pressing problems of prosthetic dentistry. Restoring rotten teeth with endocanal pins has always been one of the main problems of Dentistry. The choice of the type of needle and the determination of the number of numbers depends on the size and permeability of the canal after endodontic treatment, the number of root canals, the loss of the mass of dentin, the distance to antagonists and adjacent teeth. Needlewomen should ensure the long life of endodontic obturation, the restoration of the crown-root part of the tooth in the simplest way, taking into account the anatomy of the tooth canal. However, many doctors do not take into account the anatomical features of the loss of the dentin mass or the characteristics of the pins used. At all stages of the production of pin structures (SC), errors can be made that lead to the development of immediate or long-term complications. It is worth noting that it is impossible to talk about the advantages of pim constructions in general, it is possible to talk only about indications or contraindications for the use of a specific pin construction in a particular clinical case. in orthopedic Dentistry, the percentage of premature replacement of fixed structures remains high due to improvements in clinical techniques and technological processes, complications and unsuitable for their use. The main reasons for removing the rigid structures of dental prostheses are medical errors in the preparation of the patient's oral cavity for prosthetics, unreasonable choice of designs of prostheses and materials for them, non-compliance with the rules of treatment steps and manipulation. the use of techniques, tactical errors, imperfect technologies during odontopreparation. Therefore, the need to study this problem is urgent and timely in order to prevent and eliminate clinical errors, as well as to avoid complications that arise in the orthopedic treatment of patients with defects in the crown of the teeth with pin structures.